2010
DOI: 10.1086/656281
|View full text |Cite
|
Sign up to set email alerts
|

Multicity Outbreak of Linezolid‐ResistantStaphylococcus epidermidisAssociated with Clonal Spread of acfr‐Containing Strain

Abstract: We report a multicity outbreak of cfr-containing linezolid-resistant Staphylococcus epidermidis in Ohio. Thirty-nine isolates were obtained from 2 hospitals. Two clones with different mechanisms of linezolid resistance were circulating in hospital A. One of these contained the cfr gene, and the other a ribosomal mutation. The clone containing cfr was identical in both hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 30 publications
1
54
1
1
Order By: Relevance
“…This mutation has been reported in both staphylococci and enterococci (6,15,34,40,59,61,70,71,87,97,101), and a clear correlation between the number of mutated rRNA operons and the linezolid MIC has been found (2,35,59). Most reports of the G2576U mutation in clinical isolates are associated with some form of increased or prolonged linezolid treatment or with high linezolid usage at the local hospital (29,84), underscoring the importance of judicious use of linezolid in clinical settings.…”
Section: Resistance Caused By 23s Rrna Mutationsmentioning
confidence: 96%
See 2 more Smart Citations
“…This mutation has been reported in both staphylococci and enterococci (6,15,34,40,59,61,70,71,87,97,101), and a clear correlation between the number of mutated rRNA operons and the linezolid MIC has been found (2,35,59). Most reports of the G2576U mutation in clinical isolates are associated with some form of increased or prolonged linezolid treatment or with high linezolid usage at the local hospital (29,84), underscoring the importance of judicious use of linezolid in clinical settings.…”
Section: Resistance Caused By 23s Rrna Mutationsmentioning
confidence: 96%
“…This strain is notable because these two rRNA methyltransferase genes are located on the same operon and their coexpression confers resistance to all clinically relevant antibiotics that target the large ribosomal subunit (81). A number of staphylococcal clinical isolates containing cfr in different genetic contexts and parts of the world have subsequently been reported (5,6,16,17,65,67,72,80). In some instances, a connection between the resistant isolates and prior linezolid treatment (6,64) or extensive use of linezolid (72) can be documented.…”
Section: Resistance Caused By Alterations In 23s Rrna Modificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Linezolid resistance is mainly due to mutations in domain V of the 23S rRNA gene, among which G2567U occurs most frequently (Bonilla et al, 2010;Marshall et al, 2002). In addition, the mutations T2500A (Meka et al, 2004), C2534T (LaMarre et al, 2013, G2215A (Kosowska-Shick et al, 2010), T2504A and G2447T (Wong et al, 2010) have been reported among clinical isolates.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in 23S rRNA implicated in linezolid resistance include not only bases near the binding site, like G2061, C2452, A2503, U2504, and G2505, but also bases that are located more distantly from the binding site, such as A2062, G2447, A2453, C2499, U2500, and G2576 (reviewed in reference 8). Additional mechanisms include acquisition of the cfr gene, which encodes a methyltransferase which modifies A2503 in 23S rRNA, and a mutation in the RlmN gene, which naturally modifies A2503 (8)(9)(10)(11)(12)(13)(14). Recently, four nosocomial Staphylococcus epidermidis isolates belonging to the same pulsed-field gel electrophoresis type were described to exhibit partial linezolid dependence, an adaptation reported for only a few antibiotics and bacterial species in the past (15).…”
mentioning
confidence: 99%